Evolution of Azerbaijani Science Fiction and Emin Mahmudov - Gunel Alasgarova (Comparative Turkish Dialects and Literatures)
The evolution of science fiction literature in Azerbaijan has been characterized by a delayed emergence compared to European, American, and Russian counterparts. Despite this initial lag, Azerbaijani science fiction writers have made commendable strides, drawing influence from both global and local literary traditions. This article explores the historical context and thematic concerns of Azerbaijani science fiction literature, analyzing the impact of influential global authors on Azerbaijani writers and examining the stylistic elements present in their works. Additionally, the article delves into the life and career of Emin Mahmudov (1925-2010), a prominent Azerbaijani writer celebrated for his contributions to the genre. Mahmudov’s vivid imagination, intellectual depth, and exploration of cosmic themes have left an indelible mark on Azerbaijani literature. Through an exploration of Mahmudov’s works, such as “Prisoners of Neptune” and “Turbulence,” which delve into existential questions amidst rapid cosmic voyages, this article sheds light on the unique trajectory of science fiction literature in Azerbaijan and its broader significance within the global literary landscape.